2022
DOI: 10.3390/su14020730
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance Mechanisms on the Commitment of Managers in an IPO Setting: Evidence from Korean Small and Venture Firms

Abstract: Managers’ commitment and dedication crucially affect the sustainable growth of firms. When private companies first offer their shares to the public in an initial public offering (IPO), an IPO lockup is one way of revealing managers’ commitments. IPO lockups are agreements that promise not to sell the shares retained by pre-IPO shareholders for a specified period in the market after the IPO. This paper investigates the impact of corporate governance mechanisms on the length of the lockup period. The paper’s sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…Struktur manajemen emiten dapat menjadi perangkat komitmen yang melengkapi tata kelola perusahaan dalam mengurangi kekhawatiran investor terhadap moral hazard. (Lee, 2022).…”
Section: Pengaruh Ipo Terhadap Nilai Perusahaan Dan Good Corporate Go...unclassified
“…Struktur manajemen emiten dapat menjadi perangkat komitmen yang melengkapi tata kelola perusahaan dalam mengurangi kekhawatiran investor terhadap moral hazard. (Lee, 2022).…”
Section: Pengaruh Ipo Terhadap Nilai Perusahaan Dan Good Corporate Go...unclassified
“…Similarly ,due to the historically most significant leak of its shareholder's data for owning offshore companies which was provided Mossack Fonseca on 3 April 2016, it's found that shareholders include many political and influential figures around the globe, which causes a moral hazard (Adeel Nasir et al,2022). Examining the Impact of Corporate Governance Mechanisms on the Commitment of Managers, Youngjoo Lee(2022) suggested that managers may use the IPO lockup as a commitment device that complements corporate governance mechanisms in reducing investor concern about the moral hazard problem of managers when small and venture companies go public. Because social responsibility is essential to the sustainable development of megaprojects, Feng Xue et al(2022) argued that incentive contracts with multiple indicators in stages can effectively encourage subcontractors to disclose social responsibility information, and reduce information asymmetry, therefore enhancing social responsibility and improving overall project efficiency.…”
Section: Moral Hazardmentioning
confidence: 99%
“…Corporate governance is a necessary form of financial regulation and establishes organizational behaviour when there are imperfect relationships between market forces and institutional factors in relation to ethical responsibilities (Choudhury and Harahap, 2007). Additionally, corporate governance represents a system in which companies are directed and controlled to organize the relationships among high-level managers, shareholders, and interest groups within the framework of corporate transparency and to protect the rights of stakeholders (Arslantas & Findikli, 2013, Lee, 2022. Corporate governance manifests as a system that includes laws, rules, and factors that control the operations of a company (Gillan & Starks, 1998).…”
Section: Corporate Governancementioning
confidence: 99%